Histological Changes in Stems of Pinus sylvestris Seedlings Infected with a Virulent Isolate of the Pinewood Nematode Bursaphelenchus xylophilus - Vieira da Silva, Inês (2016)
Abstract: Bursaphelenchus xylophilus (Steiner and Buhrer) Nickle, the pinewood nematode (PWN) responsible for pine wilt disease (PWD), has become a serious threat to global pine forests. It is native from North America, where is not associated with any pathology, but when introduced in the Far East induced a disease with severe environmental and economic impacts. In Europe, PWN was first detected in maritime pine, Pinus pinaster Aiton, at Setubal peninsula (Portugal) and, currently all the country is considered a quarantine area for PWN, representing an increasingly risk of spread to European forests. The vector, a cerambycid beetle, Monochamus galloprovincialis Olivier, carries the nematode from injured to healthy trees, through feeding wounds. After invading pine trees, nematodes feed from the plant tissues and multiply rapidly [1 and ref. cit. therein]. Although extensive research has been conducted in this disease, particularly in countries in which their own forest have been devastated, a detailed mechanism of the PWN invasion is still not well described. Therefore, the present work aimed to study the histological changes induced by B. xylophilus in Pinus sylvestris L. seedling tissues.